Urgensi Penetapan Garis Pangkal Laut dalam Validasi Hukum Zona Ekonomi Eksklusif Indonesia: Tinjauan Atas Sengketa Maritim - Lovira; Rara Aulia Putri; Revan Adri Putra; Roberto Carlos Veriero Siregar; Zulqa Hijriyani (Journal of Islamic Law El Madani, 2025)
The determination of maritime baselines is a fundamental element in defining Indonesia’s Exclusive Economic Zone (EEZ). As an archipelagic state with over 17,000 islands, Indonesia requires precise and internationally recognized baselines to legitimize maritime jurisdiction, protect sovereignty, and secure marine resources. This study comprehensively examines the role of maritime baselines as a legal foundation for the delimitation of Indonesia’s Exclusive Economic Zone (EEZ). This study employs a normative legal approach by examining the provisions of the United Nations Convention on the Law of the Sea (UNCLOS) 1982 and Government Regulation No. 38 of 2002. Through case studies of maritime disputes with Malaysia (Ambalat Block), Vietnam (North Natuna Sea), and China (South China Sea), the research reveals that inaccurate or contested baseline determinations can trigger territorial conflicts, illegal fishing activities, and diplomatic tensions. The legal validity of baselines is crucial for Indonesia’s international legitimacy, maritime diplomacy, and sustainable resource governance. Therefore, the study recommends a multidimensional strategy involving legal reform, geospatial data modernization, precise hydrographic surveys, proactive diplomacy, and enhanced military presence in border areas. This study asserts that maritime baselines are not merely technical geographic markers, but strategic instruments in advancing Indonesia’s legal, political, and security interests amid regional geopolitical complexities.